Effect of different dye solutions on the evaluation of the sealing ability of Mineral Trioxide Aggregate. - Tanomaru Filho, Mario [UNESP]; Figueiredo, Frederick Alves; Tanomaru, Juliane Maria Guerreiro [UNESP] (FapUNIFESP (SciELO), 2005)
Alkaline materials have shown incompatibility with methylene blue dye in leakage experiments. The goal of the present study was to analyze the effect of different dyes on the evaluation of the apical sealing ability of Mineral Trioxide Aggregate root-end fillings. Fifty-six extracted human canines were submitted to root canal instrumentation and obturation. After apical resection, retrograde cavities were prepared and teeth were randomly divided into four experimental (n = 13) and two control groups (n = 2). The following root-end filling materials were used: groups 1 and 2--Pro Root MTA (Dentsply), groups 3 and 4--zinc oxide-eugenol cement (ZOE). Teeth in groups 1 and 3 were immersed in 2% methylene blue solution, while teeth in groups 2 and 4 were immersed in 0.2% rhodamine B in a reduced pressure environment for 48 hours. Teeth were then longitudinally sectioned and leakage was evaluated. Results were submitted to statistical analysis (ANOVA and Tukey's test). Group 1 presented the least leakage (p < 0.05). It was concluded that the evaluation of the sealing ability of MTA is influenced by the dye used, since this material presented better sealing ability when evaluated with Methylene Blue, but was similar to ZOE when evaluated with rhodamine B.
Keywords: aluminum derivative; calcium derivative; coloring agent; methylene blue; mineral trioxide aggregate; oxide; root canal filling material; silicate; zinc oxide eugenol; analysis of variance; chemistry; clinical trial; comparative study; controlled clinical trial; controlled study; drug combination; endodontics; human; methodology; randomized controlled trial; standard; tooth disease; Aluminum Compounds; Analysis of Variance; Calcium Compounds; Coloring Agents; Dental Leakage; Drug Combinations; Humans; Methylene Blue; Oxides; Retrograde Obturation; Root Canal Filling Materials; Silicates; Zinc Oxide-Eugenol Cement